First record of the Greek clouded yellow Colias aurorina Herrich-Schäffer, 1850 (Lepidoptera: Pieridae) for Albania - Rudi Verovnik; Miloš Popović (Natura Sloveniae)
During our field survey in the south-eastern part of the Republic of Albania, we encountered the Greek clouded yellow (Colias aurorina) at two sites, representing the first record for the species in Europe outside Greece. It was found common at one site on the Albanian side of the Grammos Mts. with possibly continuous range into northern Greece. As larval host plant of the Greek clouded yellow Astragalus thracicus was present in abundance on the northern slopes of the mountain, we consider the species as not threatened in Albania. In addition, the purple emperor (Apatura iris) and the Balkan green-veined white (Pieris balcana) were recorded for the first time in Albania.